The endomorphisms monoids of graphs of order n with a minimum degree n − 3 - Pipattanajinda, N.; Knauer, U.; Gyurov, B.; Panma, S. (Algebra and Discrete Mathematics, 2014)
We characterize the endomorphism monoids, End(G), of the generalized graphs G of order n with a minimum degree n − 3. Criteria for regularity, orthodoxy and complete regularity of those monoids based on the structure of G are given.